Research capacity of respiratory therapists: A survey of views, opinions and barriers - Concetta Martins; Chris Kenaszchuk (Canadian Journal of Respiratory Therapy, 2013)
In step with rapid advances in technology, evidence-based practice has emerged as a major contributor to the contemporary clinical decision-making process. However, processing the tremendous amount of rapidly evolving available information has proven to be challenging for many health care professionals. Respiratory therapy is no exception to the innovation, evolution and rapid advances that have occurred over the past decade, and many in the field are in an ideal position to contribute to the scholarship of the profession. This study was prompted by the lack of studies investigating the perspectives and opinions of respiratory therapists with regard to their participation in research and implementation of findings.